2023
DOI: 10.1111/pace.14836
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of left bundle branch area pacing compared to His bundle pacing as a primary pacing strategy: Systematic review and meta‐analysis

Amr Abdin,
Christian Werner,
Haran Burri
et al.

Abstract: BackgroundNovel pacing technologies, such as His bundle pacing (HBP) and left bundle branch area pacing (LBBaP), have emerged to maintain physiological ventricular activation. We investigated the outcomes of LBBP with HBP for patients requiring a de novo permanent pacing.Methods and ResultsSystematic review of randomized clinical trials and observational studies comparing LBBaP with HBP until March 01, 2023 was performed. Random and fixed effects meta‐analyses of the effect of pacing technology on outcomes wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…This result is slightly different with data from a recent meta-analysis by Abidin et al involving 9 studies which showed a slightly decreased QRS duration in the paced rhythm compared to baseline in both HBP and LBBA group. 27 However if analyzed separately in the meta-analysis, only studies with a very wide QRS complex (≥ 140 ms) have a signi cant reduction in the QRS duration after CSP implantation, while baseline QRS duration of both HBP and LBBAP groups in this study are ± 120ms. 27 Furthermore, in our study, patients who were initially attempted to have HBP implantation but failed to correct the wide QRS complex would switch to LBBAP implantation in the hope of correcting a more distal conduction abnormalities, resulting in a wide paced rhythm QRS duration in the LBBAP group.…”
Section: Discussionmentioning
confidence: 63%
“…This result is slightly different with data from a recent meta-analysis by Abidin et al involving 9 studies which showed a slightly decreased QRS duration in the paced rhythm compared to baseline in both HBP and LBBA group. 27 However if analyzed separately in the meta-analysis, only studies with a very wide QRS complex (≥ 140 ms) have a signi cant reduction in the QRS duration after CSP implantation, while baseline QRS duration of both HBP and LBBAP groups in this study are ± 120ms. 27 Furthermore, in our study, patients who were initially attempted to have HBP implantation but failed to correct the wide QRS complex would switch to LBBAP implantation in the hope of correcting a more distal conduction abnormalities, resulting in a wide paced rhythm QRS duration in the LBBAP group.…”
Section: Discussionmentioning
confidence: 63%
“…This impacted the total number of ventricular leads implanted for each patient, as well as the complexity of the implanted devices (lower rate of biventricular devices), and was likely due to the fact that performing AVJA a few weeks post-implantation, after the lead stabilization phase, substantially reduced the potential risks related to lead malfunction in patients becoming PM-dependent, making the RV backup lead unnecessary. These findings have significant clinical implications as, as shown in several studies [29,[31][32][33][34][35], the implantation of fewer leads and of less complex devices reduces the risk of infection and lead-related complications, as well as reducing the cost of the procedure. On the other hand, we observed that, during follow-up, in all study populations, CSP thresholds remained stable, and no patient in either study group experienced adverse events related to the loss of capture occurring during the stabilization phase.…”
Section: Discussionmentioning
confidence: 71%
“…Also of note, after the stabilization phase, the RV backup lead was deactivated in all LBBAP patients in both groups, as the capture thresholds remained stable. These findings could suggest that, especially in patients receiving LBBAP, which, as known, shows lower and stable capture thresholds during the follow-up compared to HBP [17,18,25,29,[31][32][33][34][35], the RV backup lead could be superfluous, even in patients in whom AVJA is performed simultaneously with the implantation.…”
Section: Discussionmentioning
confidence: 95%
“…Previous studies reported that LBBP was superior to LVSP in enhancing pacing characteristics, such as LVAT and QRS duration. 8,9 LVSP was not part of the success criteria for LBBAP in initial studies, [10][11][12][13][14][15][16][17][18][19] while the latest consensus document has included LVSP for LBBAP. 7 Recent clinical studies have demonstrated that LBBAP led to better outcomes than RVAP 10,11 ; LBBAP boasted a higher success rate and a more consistent pacing capture threshold than HBP.…”
Section: Introductionmentioning
confidence: 99%
“…7 Recent clinical studies have demonstrated that LBBAP led to better outcomes than RVAP 10,11 ; LBBAP boasted a higher success rate and a more consistent pacing capture threshold than HBP. [13][14][15][16][17][18][19][20] Although previous studies compared clinical outcomes between LBBAP and HBP, little data are available regarding the feasibility and efficacy of LBBAP in Japanese subjects. Therefore, the current study sought to investigate the clinical outcomes of LBBAP compared with HBP and RVAP in Japanese patients with bradycardia requiring permanent cardiac pacing.…”
Section: Introductionmentioning
confidence: 99%